Adult T-cell leukemia/lymphoma treatment in Bahia, Brazil - Oliveira,Pedro Dantas (2017)
Abstract Background: Adult T-cell leukemia/lymphoma is a peripheral disease associated with human T-cell lymphotropic virus type 1. Treatment is carried out according to clinical type with watchful waiting being recommended for less aggressive types. Aggressive adult T-cell leukemia/lymphoma is generally treated with chemotherapy and/or antivirals. The objective of this study was to correlate the survival of patients diagnosed in Bahia, Brazil, with the therapeutic approaches employed and to evaluate what issues existed in their treatment processes. Methods: Eighty-three adult T-cell leukemia/lymphoma patients (26 smoldering, 23 chronic, 16 acute, 13 lymphoma and five primary cutaneous tumoral) with available data were included in this study. Results: Complete response was achieved in seven smoldering patients with symptomatic treatment, in two with chronic disease using antivirals/chemotherapy, in one with acute disease using antivirals and in one lymphoma using the LSG15 regimen [vincristine, cyclophosphamide, doxorubicin, and prednisolone (VCAP); doxorubicin, ranimustine, and prednisolone (AMP); and vindesine, etoposide, carboplatin, and prednisolone (VECP)]. Smoldering patients who received symptomatic treatment presented longer survival. Favorable chronic patients treated with antivirals presented longer survival compared to the unfavorable subtype. However, for the acute form, first-line chemotherapy was better, albeit without significance, than antivirals. Only one of the patients with lymphoma and primary cutaneous tumors responded. Conclusions: Watchful waiting associated with phototherapy represents the best option for smoldering adult T-cell leukemia/lymphoma with survival in Bahia being superior to that described in Japan. There was a trend of better results with zidovudine/interferon-alpha in favorable chronic disease. Excellent results were achieved in the lymphoma type treated with the LSG15 protocol. Patients are diagnosed late probably due to lack of knowledge of adult T-cell leukemia/lymphoma by primary healthcare doctors and a Brazilian treatment protocol needs to be established.